Revisión sistemática de literatura del concepto “organización criminal” mediante el modelo PRISMA - Lizarzaburu Bolaños, Edmundo (2024)
The growth in the number of criminal organizations and their complexity, in conceptual variety, theoretical implications and empirical challenges, have made it difficult for researchers to generate sufficient theories, studies of causes and scales that allow a categorization and explanation of their phenomena. The characterization of these organizations and the approach to their definition are complex both due to the diversity of their social impacts and the wealth of the thematic areas that address them. This study shows the research and study trends of criminal organizations by conducting a systematic literature review from 2022 and 2023, using the PRISMA method and exploring current trends in academic research and bibliographic production on the subject.